Laughter in children as a function of social facilitation - De la Cruz, Beverlyn-Jean A. (1981)
This study investigated the social facilitation of laughter. Independent groups of 5 to 6-year-old children listened on headphones to amusing material under three experimental conditions: the alone condition, wherein they listened in isolation; the audience condition, wherein they listened with a non-listening companion; and the coaction condition, wherein they listened with someone who also listened to the material. Sex difference were also investigated, thus giving rise to 3 x 2 factorial design. Results were analyzed through the analysis of variance at an alpha level of .05 total time spent laughing and smiling were highest in the coaction group, and were higher in the audience than in the alone condition. No sex differences were found and no interaction effects occured between the two variables.
Includes bibliographic references.
Keywords: Laughter; Social psychology